2009
DOI: 10.1590/s0102-76382009000100013
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrências clínicas no membro submetido à exérese de veia safena magna para revascularização do miocárdio

Abstract: Intercorrências clínicas no membro submetido à exérese de veia safena magna para revascularização do miocárdioClinical complications of limb undergone harvesting of great saphenous vein for coronary artery bypass grafting using bridge technique Abstract Objective: The aim of this study was to assess clinical complications of limbs undergone harvesting of the great saphenous vein for venous coronary artery bypass graft surgery using bridge technique.Methods: Fourty-four patients who had undergone CABG using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…However, Khoshgoftar et al concluded in their study that changing leg posture, being out of bed and walking 24 hours after the operation and lower limb physiotherapy had no significant effect on donor limb edema ( 16 ). Diuretic use and the history of diabetes mellitus had no effect on the incidence of lower limb edema 4 weeks after the operation, similar to the studies of Khoshgoftar et al ( 16 ) and Belczak et al ( 18 ). Our study also revealed that there was no relation between the low sodium diet and the incidence of edema 4 weeks post-op.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, Khoshgoftar et al concluded in their study that changing leg posture, being out of bed and walking 24 hours after the operation and lower limb physiotherapy had no significant effect on donor limb edema ( 16 ). Diuretic use and the history of diabetes mellitus had no effect on the incidence of lower limb edema 4 weeks after the operation, similar to the studies of Khoshgoftar et al ( 16 ) and Belczak et al ( 18 ). Our study also revealed that there was no relation between the low sodium diet and the incidence of edema 4 weeks post-op.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of wound complications at the site of saphenous vein harvesting had no effect on the incidence of the lower limb edema in our study. In the study of Belczak et al the incidence of suture infection at lower limb after CABG surgery was reported 25%; however, its relation with the incidence of edema was not evaluated ( 18 ). There was no relation between the method of saphenous vein harvesting and the incidence of edema four weeks after the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…Study published in this journal reported on complications after saphenous vein harvesting such as paresthesia, lymphorrhea, infection and deep venous thrombosis [1]. Another study in this journal showed that leg wound complications were observed more in the traditional long incision vein harvesting technique (P=0.0005).…”
mentioning
confidence: 91%